Impact of healthcare-associated infection on length of stay. (August 2021) - Stewart, S.; Robertson, C.; Pan, J.; Kennedy, S.; Haahr, L.; Manoukian, S.; Mason, H.; Kavanagh, K.; Graves, N.; Dancer, S.J.; Cook, B.; Reilly, J.
Summary: Background: Increased length of stay (LOS) for patients is an important measure of the burden of healthcare-associated infection (HAI). Aim: To estimate the excess LOS attributable to HAI. Methods: This was a one-year prospective incidence study of HAI observed in one teaching hospital and one general hospital in NHS Scotland as part of the Evaluation of Cost of Nosocomial Infection (ECONI) study. All adult inpatients with an overnight stay were included. HAI was diagnosed using European Centres for Disease Prevention and Control definitions. A multi-state model was used to account for the time-varying nature of HAI and the competing risks of death and discharge. Findings: The excess LOS attributable to HAI was 7.8 days (95% confidence interval (CI): 5.7–9.9). Median LOS for HAI patients was 30 days and for non-HAI patients was 3 days. Using a simple comparison of duration of hospital stay for HAI cases and non-cases would overestimate the excess LOS by 3.5 times (27 days compared with 7.8 days). The greatest impact on LOS was due to pneumonia (16.3 days; 95% CI: 7.5–25.2), bloodstream infections (11.4 days; 5.8–17.0) and surgical site infection (SSI) (9.8 days; 4.5–15.0). It is estimated that 58, 000 bed-days are occupied due to HAI annually. Conclusion: A reduction of 10% in HAI incidence could make 5800 bed-days available. These could be used to treat 1706 elective patients in Scotland annually and help reduce the number of patients awaiting planned treatment. This study has important implications for investment decisions in infection prevention and control interventions locally, nationally, and internationally.